Tau lepton averages by the HFLAV group - Alberto Lusiani (SciPost Physics Proceedings)
We document some features of the preliminary draft of the tau lepton averages for the incoming HFLAV report. We include the tau mass and lifetime averages, and a fit of measurements of tau branching fraction measurements. Elaborations of these results provide lepton universality tests and determination of $|V_{us}|$ with tau measurements.